2008
DOI: 10.1007/s10278-008-9128-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Radcube for Extraction of Finding Trends in a Large Radiology Practice

Abstract: The purpose of our study was to demonstrate the use of Natural Language Processing (Leximer), along with Online Analytic Processing, (NLP-OLAP), for extraction of finding trends in a large radiology practice. Prior studies have validated the Natural Language Processing (NLP) program, Leximer for classifying unstructured radiology reports based on the presence of positive radiology findings (F (POS)) and negative radiology findings (F (NEG)). The F (POS) included new relevant radiology findings and any change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…In our entire sample, there were 307 300 abdominal CT scans, of which 49 145 (16%) had at least one RAI. One reason for our lower rate could be that the automated NLP method for detecting RAI may be somewhat insensitive compared with manual abstraction, though our method studies have consistently yielded sensitivities well above 90% (9)(10)(11)(12)(13)(14). However, if our NLP method had a systematic and consistent false-negative rate for RAI, it would not affect odds ratio estimates, and our inferences based on them would hold true.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…In our entire sample, there were 307 300 abdominal CT scans, of which 49 145 (16%) had at least one RAI. One reason for our lower rate could be that the automated NLP method for detecting RAI may be somewhat insensitive compared with manual abstraction, though our method studies have consistently yielded sensitivities well above 90% (9)(10)(11)(12)(13)(14). However, if our NLP method had a systematic and consistent false-negative rate for RAI, it would not affect odds ratio estimates, and our inferences based on them would hold true.…”
Section: Discussioncontrasting
confidence: 47%
“…We specifically excluded generic statements such as "clinical correlation," as well as those calling for correlation with surgery, biopsy, or endoscopy and/or colonoscopy. The same NLP system also produces an output for each report that codes any clinically important findings and returns "negative" when none are detected in the text (9,10,14). This was used to create a "positive findings" variable for subsequent analysis with values of yes and no.…”
Section: Implication For Patientmentioning
confidence: 99%
See 2 more Smart Citations
“…Dang et al employed NLP/NLU technologies to find trends in a large radiology practice (Dang et al, 2009). Experimental results showed that NLP/NLU technologies could help to analyze yield of different radiology exams from a large radiology report database based on presence of positive/negative radiology findings.…”
Section: Applications Of Machine Learning In Radiologymentioning
confidence: 99%